Teacher–student dialogue: transforming teacher interpersonal behaviour and pedagogical praxis through co-teaching and co-generative dialogue - Rahmawati, Y.; Koul, Rekha; Fisher, D. (Kluwer Academic Publishers, 2015)
The paper reports a study of the effectiveness of co-teaching and co-generative dialogue in science learning and teaching in lower secondary science classes. The idea of co-teaching and co-generative dialogue—first proposed by two leading educationists, Roth and Tobin, in early 2000—made an international impact in educational research. In the context of the research, co-teaching and co-generative dialogue were applied for transforming teacher interpersonal behaviour. The pre-validated Questionnaire on Teacher Interaction (QTI) was administered to all the year nine classes at three selected secondary schools to investigate existing teacher interpersonal behaviours and to further validate the QTI. This was followed by the implementation of co-teaching and co-generative dialogue in three selected science classrooms, one from each school. Multiple research methods (interview, students’ reflective journals, and questionnaire) were used to develop in-depth understanding of the participants. Co-teaching and co-generative dialogue helped in transforming teacher interpersonal behaviour and teachers’ pedagogical praxis. This process also had implications for improving students’ engagement, achievement and behaviour.